2018
DOI: 10.1002/pds.4619
|View full text |Cite
|
Sign up to set email alerts
|

Comparative out‐of‐hospital mortality of long‐acting opioids prescribed for non‐cancer pain: A retrospective cohort study

Abstract: In the study population, long-acting opioids for non-cancer pain were associated with high out-of-hospital mortality rates. We found comparable out-of-hospital mortality risks associated with transdermal fentanyl and morphine SR. The risk of out-of-hospital death for oxycodone CR was lower than that for morphine SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 28 publications
(46 reference statements)
0
12
0
2
Order By: Relevance
“… 26 The risk of increased out-of-hospital mortality was higher in patients using morphine and fentanyl than in those using oxycodone in another cohort study of the same group. 175 Importantly, opioids (including tramadol) were demonstrated to cause higher risk of mortality among patients treated for chronic non-malignant pain than NSAIDs. 25 , 176 The risk of opioid-related death may be increased with the use of long-acting opioids, at a higher dose range, within 4 weeks after opioid initiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 The risk of increased out-of-hospital mortality was higher in patients using morphine and fentanyl than in those using oxycodone in another cohort study of the same group. 175 Importantly, opioids (including tramadol) were demonstrated to cause higher risk of mortality among patients treated for chronic non-malignant pain than NSAIDs. 25 , 176 The risk of opioid-related death may be increased with the use of long-acting opioids, at a higher dose range, within 4 weeks after opioid initiation.…”
Section: Resultsmentioning
confidence: 99%
“…27 However, a number of individual epidemiological investigations published so far indicated that patients treated with opioids for chronic pain may be susceptible to a higher risk of injuries, poisoning and mortality. 25,26,132,[171][172][173][174][175][176][177][178][179][180] For example, in a trial concerning approximately 10,000 patients with chronic non-malignant pain treated with opioids, 51 cases of opioid overdose, including 6 (12%) opioidrelated deaths, were identified. Patients receiving ≥100 mg of MEDD had a 1.8% annual overdose rate.…”
Section: Dovepressmentioning
confidence: 99%
“…The practice of data linkage for complete outcome ascertainment is well‐known to pharmacoepidemiologists following the guidelines for good pharmacoepidemiology practice . Recent work by Chung et al in TennCare data highlights the ascertainment of out‐of‐hospital death in an opioid study by linking to state‐specific computerized death certificate data. Data linkage is likely pivotal in a majority of our health system databases to identify outcomes, particularly for mortality.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, long-acting opioid use has been correlated with increased risk of serious infection, with patients given oxycodone demonstrating a lower rate of infection than those prescribed morphine (Wiese et al, 2018). Additionally, a large retrospective cohort study recently reported that the risk of outof-hospital death was lower in those filling long-acting oxycodone than in those filling long-acting morphine, potentially pointing to an association between type of opioid prescribed and subsequent mortality outcomes (Chung et al, 2019).…”
mentioning
confidence: 99%